Filter Halaman Web Pornografi Menggunakan Kecocokan Kata dan Deteksi Warna Kulit - Rijal, Yusron; Nofitasari, Awalia (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2011)
This paper presents an effort to detect pornographic webpages. It was stated that a positive relationship exists between percentage of human skin color in an image and the image itself (Jones et.al., 1998). Based on the statement, rather than using the traditional method of text-filtering, this paper propose a new approach to detect pornographic images by using skin color detection. The skin color detection performed by using RGB, HSI, and YCbCr color model. Using algorithm stated by Ap-apid (Ap-apid, 2005), the system will classify nude and not-nude images. If one or more nude images are found, the system will block the webpage. Keywords: Webpage Filtering, Image Processing, Pornography, Nudity, Skin Color, Nude Images